The Urgency of Arabic for Religious Court Judges in Indonesia - Chintya, Aprina; Adila, Rasikh (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
As a judicial institution based on Islamic law, the religious court is a special court which is only authorized in certain areas of civil, not including the criminal field (except Aceh province) for Moslems. Therefore, Islamic law and Arabic language should become a daily routine for judges. This study was designed to gain an in-depth understanding of Arabic urgency for religious court judges in Indonesia and how those language skill affect the  duties and responsibilities of religious court judges. Arabic plays an important role in the religious court because Arabic is the language of the Holy Quran and other Islamic laws. The judges considered Arabic very high esteem with most of their duties and responsibilities were inseparable from Arabic. Governments have been offering scholarships and other opportunities for judges who are interested in Arabic studies and Islamic studies in the Middle East.